Análisis de factibilidad financiera de un proyecto de gasificación de biomasa forestal para la generación de 2MW de potencia en Costa Rica - González-Barboza, Jerson (Instituto Tecnológico de Costa Rica, 2016)
This work is based on the analysis of existing information in order to identify the role that forest biomass plays for power generation with existing technologies. The adequate thermochemical process was identified in the electricity generation of medium power for energy supply in Costa Rican industries with consumption in the range of 1, 8 to 3, 8 MW. The chosen technology was downdraft fixed bed gasification, with a generating capacity of 2 MW. The plant supply took into consideration 67 USD/t as biomass productive cost having a plantation as the wood energy crops. However, the system's profitability was reached with the purchase of biomass to third parties. The financial analysis of the plant took into account two scenarios for its implementation, where selling energy to the Instituto Costarricense de Electricidad (Costa Rican Electricity Institute) was not profitable. The opposite case was the generation for self-consumption, where the internal rate of return obtained was 17, 68%.
Proyecto de Graduación (Licenciatura en Ingeniería Forestal) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería Forestal, 2016.
Keywords: Termoquímica; Biomasa; Energía; Research Subject Categories::FORESTRY, AGRICULTURAL SCIENCES and LANDSCAPE PLANNING::Plant production::Plant and forest protection